Cardiac arrest following chlormethiazole infusion in chronic alcoholics. Issue 660 (October 1980) - McInnes, G. T.; Young, R. E.; Avery, B. S.
Abstract : Two chronic alcoholics who had cardiac arrests (one fatal) while receiving chlormethiazole by infusion are reported. Although a causal relationship has not been indisputably established, caution is advised when administering this drug to chronic alcoholics during withdrawal.